(untitled) (Costa Rican Journal of Guidance & Counseling, 2024)
Objective: Obtain evidence of validity and reliability of the scale for measuring employability skills in students of the third and fourth level of high school in 2022, in accredited courses of the National University. Methodology: It is based on the quantitative paradigm, with a non-experimental design and a descriptive scope. The sample included 335 active students in the II school year of 2022. The design of the EMCE included three phases: a) determination of the profile of employability competencies, b) standardization of employability competencies, and c) instrumentation of the scale. The statistical analysis of validity and reliability was performed using Jamovi software in version 2.4.14. Results: Content validity by expert judgment showed that the EMCE meets the criteria of clarity, coherence, relevance, and sufficiency. The validation of internal structure, with the Bartlett Test (< .001) and the KMO Index (0.919), indicated that Exploratory Factor Analysis (EFA) is appropriate. The EFA suggests that the first three factors manage to explain 40.6% of the variability of the EMCE construct. Reliability presented a Cronbach’s alpha coefficient (0.94) and a McDonald’s omega coefficient (0.943), confirming high internal consistency. Conclusions: The EMCE proves to be a valid and reliable tool to measure employability skills in university students according to predefined performance criteria.